Two new cave-dwelling species of the short-tailed Whipscorpion genus Rowlandius (Arachnida: Schizomida: Hubbardiidae) from northeastern Brazil, with comments on male dimorphism. - Adalberto J Santos; Rodrigo Lopes Ferreira; Bruno A Buzatto (PLoS ONE, 2013)
Two new species of the arachnid order Schizomida, Rowlandius ubajara sp.nov. and Rowlandius potiguar sp.nov., are described based on both male and female specimens collected in caves from northeastern Brazil. Rowlandius ubajara is known only from the Ubajara Cave, in the state of Ceará; R. potiguar is recorded from 20 caves of the Apodi Limestone Group, in the state of Rio Grande do Norte. A remarkable dimorphism in male pedipalp length is described and analyzed in R. potiguar. The distribution of male pedipalp length is clearly bimodal in the species, but the two male morphs (homeomorphic and heteromorphic) present some overlap in the sizes of this structure. Moreover, males show a steeper allometry in pedipalp length than females, indicating that this trait is under a different selective regime in males and in females.